Analysis of Factors Influencing Generation Z Visits to Health Service Centers - Edy Gunawan; Lalu Sulaiman; Karjono Karjono (Indonesian Journal of Global Health Research, 2024)
Generation Z's use of technology in health services is very significant in various aspects, including access to information, health services, and interactions with doctors or other health workers. The Republic of Indonesia has guaranteed health for all generations in the implementation of the health service system through the 1945 Constitution and Health Law number 17 of the year. This study aims to determine the factors that influence the level of generation Z sick visits to health service centers in Bima Regency, NTB. The importance of conducting this research is because the level of sick visits by generation Z at health service centers in Bima Regency is not yet optimal and the use of smart phones by generation Z in accessing health information is indicated by the low number of visits by Generation Z which can hinder the realization of the vision of a golden Indonesia 2045. Research according to the level of explanation consists of: Associative research is research that focuses on finding relationships between one variable and other variables. Selection of informants based on theory or theoretical sampling is suitable if the main objective of data collection is to develop a substantive theory. The informants in this research were 23 people. The selection of informants in qualitative research is completely determined by the researcher, so it is often called purposeful sampling, namely selecting informative cases (information rich cases) based on the strategy and objectives that the researcher has set, the number of which depends on the study objectives and resources (Heryana, 2018). Collecting data obtained from the results of interviews and observations as well as documentation recorded in field notes, data reduction with the aim of concluding the data then sorting the data into units of concepts and categories and certain themes, and presenting data which has been reduced and categorized and represented in a form that is easier to understand. This research was carried out by reducing data, displaying data and drawing conclusions to the point of saturation. In Bima, Generation Z who are active in the digital world and social media prefer to seek health information independently through health applications and social platforms such as Tik-tok and Instagram, rather than coming directly to health facilities, especially for minor health problems. in Bima Regency. Factors such as distance, condition of road infrastructure, availability of transportation, and location of health facilities greatly influence the ease or difficulty of access. Generation Z tends to look for health facilities that are close, have complete services, or are more strategic to save time and energy. As a group transitioning towards financial independence, Generation Z tends to consider the cost of health services, availability of insurance, and quality of facilities before deciding on treatment.